KONTRIBUSI MASYARAKAT EKONOMI SYARIAH DALAM DISTRIBUSI MINYAK GORENG - Herlina (Al-Iqtishad: Jurnal Ekonomi Syariah, 2022)
The phenomenon of scarcity of cooking oil began to roll at the end of the year and prices have not returned to normal until now. Several community groups experienced panic buying and this triggered the Islamic economic community consisting of ulama and Islamic community movements to take part in overcoming the problem of cooking oil by distributing it to various places for free and at low prices. The purpose of this study is to reveal the types and efforts of the Islamic economic community in distributing cooking oil so that their needs are met. This research method uses a qualitative approach. Research types and strategies include case studies and phenomenology. The research period is from the end of 2021 to June 5, 2022. Data collection and collection is more dominant in participant observer observation. Research analysis on the activities of the Islamic economic community uses social media data, namely news, youtube and some relevant references. This research is classified as field research. The results of the study found the right distribution pattern and behavior of the Islamic economic community in overcoming the scarcity of cooking oil in the market and the wider community by carrying out alms programs, cheap markets, establishing command posts and cutting distribution chains. Good collaboration and coordination between the government, distributors and the Islamic economic community is very much needed in dealing with and overcoming the cooking oil polemic.